Therapeutic potential of mackerel-derived peptides and the synthetic tetrapeptide TVGF for sleep disorders in a light-induced anxiety zebrafish model - Wang, Yang; Gu, Lei; Zhang, Haijing; Wang, Junbao; Wang, Xichang; Li, Yu; Chai, Shiwei; Xu, Changhua (Frontiers in Pharmacology, 2024)
Introduction Anxiety-like insomnia is a known risk factor for the onset and worsening of certain neurological diseases, including Alzheimer’s disease. Due to the adverse effects of current anti-insomnia medications, such as drug dependence and limited safety, researchers are actively exploring natural bioactive compounds to mitigate anxiety-like insomnia with fewer side effects. Mackerel (Pneumatophorus japonicus), a traditional Chinese medicine, is known for its tonic effects and is commonly used to treat neurasthenia. The use of mackerel protein extract has been shown to effectively improve symptoms of light-induced anxiety-like insomnia in a zebrafish model. Methods This study examines the effects of mackerel bone peptides (MW < 1 kDa, MBP1) and the synthetic peptide Thr-Val-Gly-Phe (TVGF) on light-induced anxiety-like insomnia in zebrafish. The evaluation is conducted through behavioral observation, biochemical marker analysis, and gene transcriptome profiling. Results MBP1 significantly alleviated abnormal hyperactivity and restored neurotransmitter levels (dopamine and γ-aminobutyric acid) to normal. Moreover, it mitigated oxidative stress by reducing reactive oxygen species production and malonaldehyde levels, while enhancing antioxidant enzyme activities (superoxide dismutase and catalase). This was further attributed to the regulation of lipid accumulation and protein homeostasis. Furthermore, MBP1 ameliorated sleep disturbances primarily by restoring normal expression levels of genes involved in circadian rhythm (per2 and sik1) and visual function (opn1mw2, zgc:73075, and arr3b). Molecular docking analysis indicated that TVGF exhibited good affinity for receptors linked to sleep disturbances, including IL6, HTR1A, and MAOA. TVGF exhibited sedative effects in behavioral assays, mainly mediated by regulating the normal expression of genes associated with circadian rhythm (cry1bb, cry1ba, per2, per1b and sik1), visual function (opn1mw1, gnb3b, arr3b, gnat2), purine metabolism (pnp5a), and stress recovery (fkbp5). Discussion These findings suggest that MBP1 and TVGF could be promising therapies for light-induced anxiety-like insomnia in humans, offering safer alternatives to current medications. Additionally, the regulation of genes related to circadian rhythm and visual perception may be a key mechanism by which MBP1 and TVGF effectively relieve anxiety-like insomnia.